Quench–drive spectroscopy of cuprates. (9th June 2022) - Puviani, Matteo; Manske, Dirk
Abstract : We calculate the nonlinear signal of a cuprate superconductor when subjected to a quenching and a driving field, showing transient features of the generated higher harmonics, as well as the enhancement of coherence in incoherent Cooper pairs. Abstract : Cuprates are d-wave superconductors which exhibit a rich phase diagram: they are characterized by superconducting fluctuations even above the critical temperature, and thermal disorder can reduce or suppress the phase coherence. However, photoexcitation can have the opposite effect: recent experiments have shown an increasing phase coherence in optimally doped BSCCO with mid-infrared driving. Time-resolved terahertz spectroscopies are powerful techniques to excite and probe the non-equilibrium states of superconductors, directly addressing collective modes, such as amplitude (Higgs) oscillations. In this work, we calculate the full time evolution of the current generated by a cuprate with a quench–drive spectroscopy setup. Analyzing the response in Fourier space with respect to both the real time and the quench–drive delay time, we look for the signature of a transient modulation of higher harmonics, as well as the Higgs mode, in order to characterize the ground state phase. In particular, this approach can provide a smoking gun for induced or increased phase coherence when applied to the pseudogap phase. These results can pave the way for future experimental schemes to characterize and study superconductors alongside incoherent phases and phase transitions, including induced and transient superconductivity.